Pengaruh Paparan Hipoksia terhadap Aktivitas Antioksidan Katalase dan Kadar Malondialdehid (MDA) pada Jaringan Hati Tikus - Puspitaningrum, Rini; Lestari, Amanda Putri; Murtiati, Tri (LPPM Universitas Negeri Jakarta, 2014)
Abstract content in the tissue. Hypoxia can make the formation of free radicals or reactive oxygen species (ROS) which reactive to cell membrane. Body will avoid free radicals by producing antioxidant, such as catalase enzyme. The reaction between ROS and cell membrane will form malondialdehyde (MDA). Liver is the main location of catalase. This research was aimed to know the influence of hypoxia exposure toward catalase antioxidant activity and MDA content in the rat liver tissue. This research used experiment method with fully randomized design. Based on one way Anova test (pâ‰¤0.01), it was shown that there had no average difference on catalase activity and MDA content toward length hypoxia exposure. The conclusion of this research was no influence of hypoxia exposure toward catalase activity and MDA content in rat liver tissue. Key words: catalase antioxidant activity, hypoxia, malondialdehyde (MDA) content,rat liver tissue